Pro-Palestinian netizen cyber activism through the Julid Fi Sabilillah movement on Instagram - Amrullah, Haekal Fajri; Bate, Andi Pajolloi; Briandana, Rizki (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study investigates the Julid Fi Sabilillah movement, a pro-Palestinian cyber activism initiative on Instagram formed by Indonesian netizens in response to the Al-Aqsa Hurricane attack by Israel. The emergence of a social movement on social media called Julid Fi Sabilillah became a mutually supportive virtual community that was formed to fight Israeli propaganda and its supporters on social media by trolling, cursing, and terrorizing the social media accounts of Israeli supporters. This research aims to find out and analyze how Julid Fi Sabilillah's activism on Instagram social media creates propaganda and mental attacks and creates negative issues for Israeli supporters on social media. Using a qualitative approach and case study method, this research revealed that the Julid Fi Sabilillah movement successfully countered the narrative supporting Israel on Instagram. Findings reveal that the movement has effectively disrupted pro-Israel accounts, causing psychological distress among supporters and amplifying global awareness of Palestine's plight. This digital activism highlights the potential of social media in uniting global efforts toward political and humanitarian causes. ***** Penelitian ini menyelidiki gerakan